PENGARUH PRODUCT MIX PRICING STRATEGY TERHADAP KEPUTUSAN MENGINAP DI ANGGREK SHOPPING HOTEL BANDUNG (Survei Terhadap Tamu Individu yang Menginap di Anggrek Shopping Hotel Bandung) - Rahayu, Riane; Novalita, Dewi Pancawati (Universitas Pendidikan Indonesia, 2013)
There are shopping hotel in Bandung, which are Hyatt Regency Hotel, Sensa Hotel, Aston Braga Hotel Apartement, Harris Hotel, BTC Hotel and Anggrek Shopping Hotel. Anggrek Shopping Hotel is one of the hotel with two stars classification which is located in heart of the city of Bandung in Martadinata street number 15 where is connecting directly with Riau Junction shopping mall with only 41 rooms and better service than before. Over last two years with new mangement, Anggrek Shopping Hotel is still has fluctuatif occupancy, so that in third years internal management make a new strategy on product and pricing for the guest. The responden of this research is individuals guest who stay in Anggrek Shopping Hotel Bandung. This research was conducted for two months, from September 2012 until October 2012. This type of study is a descriptive and verifikatif, and for method are using survey explanatory method ans simple random sampling technique, and for number of samples to be studies were 100 respondens. The data analysis technique is regression with SPSS 17.0 as the computer software. The data collection technique are interviews and questionnaire distribution. The finding of this research is there an impact of product mix pricing strategy which consists of product line pricing, optional product pricing, and product bundle pricing. On decision to stay. The dimension of product mix pricing strategy which has the highest influence is product bundle pricing and the one with lowest influence is product line pricing. While the most appealing factor of decision to stay is product and service. Suggestion to Anggrek Shopping Hotel Bandung is about internal facilities to increase the interest to stay in Anggrek Shopping Hotel Bandung.